Next‐generation ARIA care pathways for rhinitis and asthma: a model for multimorbid chronic diseases. Issue 1 (9th September 2019) - Bousquet, J. Jean; Schünemann, Holger J.; Togias, Alkis; Erhola, Marina; Hellings, Peter W.; Zuberbier, Torsten; Agache, Ioana; Ansotegui, Ignacio J.; Anto, Josep M.; Bachert, Claus; Becker, Sven; Bedolla‐Barajas, Martin; et al.
Abstract: Background: In all societies, the burden and cost of allergic and chronic respiratory diseases are increasing rapidly. Most economies are struggling to deliver modern health care effectively. There is a need to support the transformation of the health care system into integrated care with organizational health literacy. Main body: As an example for chronic disease care, MASK (Mobile Airways Sentinel NetworK), a new project of the ARIA (Allergic Rhinitis and its Impact on Asthma) initiative, and POLLAR (Impact of Air POLLution on Asthma and Rhinitis, EIT Health), in collaboration with professional and patient organizations in the field of allergy and airway diseases, are proposing real‐life ICPs centred around the patient with rhinitis, and using mHealth to monitor environmental exposure. Three aspects of care pathways are being developed: (i) Patient participation, health literacy and self‐care through technology‐assisted "patient activation", (ii) Implementation of care pathways by pharmacists and (iii) Next‐generation guidelines assessing the recommendations of GRADE guidelines in rhinitis and asthma using real‐world evidence (RWE) obtained through mobile technology. The EU and global political agendas are of great importance in supporting the digital transformation of health and care, and MASK has been recognized by DG Santé as a Good Practice in the field of digitally‐enabled, integrated, person‐centred care. Conclusion: In 20 years, ARIA has considerably evolved from the first multimorbidity guideline in respiratory diseases to the digital transformation of health and care with a strong political involvement.